Schizorhynchia Meixner, 1928 (Platyhelminthes, Rhabdocoela) of the Iberian Peninsula, with a description of four new species from Portugal - Gobert, Stefan; Monnens, Marlies; Eerdekens, Lise; Schockaert, Ernest; Reygel, Patrick; Artois, Tom (European Journal of Taxonomy, 2020)
During several sampling campaigns in the regions of Galicia and Andalusia in Spain and the Algarve region in Portugal, specimens of twelve species of schizorhynch rhabdocoels were collected. Four of these are new to science: three species of Proschizorhynchus (P. algarvensis sp. nov., P. arnautsae sp. nov. and P. troglodytus sp. nov.) and one species of Schizochilus (S. coninxae sp. nov.). The new species of Proschizorhynchus can be distinguished from their congeners by the curvature and length of their stylet, as well as the cirrus sheath and the organisation of the genital system. Schizochilus coninxae sp. nov. has a distinct two-part stylet that is unique within the genus. In addition to these new species, new data are reported for the diascorhynchid Diascorhynchus caligatus and the schizorhynchids Carcharodorhynchus multidentatus, C. tenuis, C. flavidus, Proschizorhynchus pectinatus and P. reniformis. Finally, new records for C. flavidus from the Hawaiian archipelago are presented.